การประเมินการแก้โจทย์ปัญหาคณิตศาสตร์เพื่อชี้นำการจัดการเรียนรู้: การประยุกต์ใช้โมเดลวินิจฉัยทางพุทธิปัญญา ASSESSING MATH WORD PROBLEM SOLVING TO GUIDE INSTRUCTION: AN APPLICATION OF COGNITIVE DIAGNOSTIC MODELING1 - ทุมมาพันธ์, พลรพี; Dong, Dongsheng; Li, Min (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การแก้โจทย์ปัญหาคณิตศาสตร์เป็นสมรรถนะสำคัญสำหรับผู้เรียนในการเชื่อมโยงความคิดรวบยอดทางคณิตศาสตร์ไปสู่สถานการณ์ในชีวิตประจำวัน แต่การประเมินการแก้โจทย์ปัญหาคณิตศาสตร์และการนำสารสนเทศจากการประเมินไปใช้ยังทำได้ไม่เต็มที่ บทความนี้มุ่งวิเคราะห์ความสามารถในการแก้โจทย์ปัญหาของนักเรียนด้วยการใช้โมเดลวินิจฉัยทางพุทธิปัญญา (Cognitive diagnostic model: CDM) ภายใต้กรอบแนวคิดเชิงบูรณาการระหว่างทฤษฎีทางพุทธิปัญญากับการวัดผล และนำเสนอแนวทางการนำสารสนเทศจากการประเมินวินิจฉัยไปใช้ในการจัดการเรียนรู้ ผู้เข้าร่วมการวิจัยเป็นนักเรียนเกรด 5 ถึง 7 จากสโมสรเด็กชายและหญิง(boys and girls clubs) ในเมืองหนึ่งของรัฐทางตะวันตกเฉียงเหนือของประเทศสหรัฐอเมริกา จำนวน 89 คน ข้อสอบที่ใช้เป็นข้อสอบหลังการเล่นเกมออนไลน์จำนวนทั้งสิ้น 11 ข้อ ซึ่งส่วนมากคัดเลือกมาจากการประเมินระดับชาติของประเทศสหรัฐอเมริกาหรือNational Assessment of Educational Progress(NAEP) ระดับเกรด 4 ของสหรัฐอเมริกา เป็นข้อสอบเลือกตอบ 6 ข้อ และเขียนตอบ 5 ข้อ ข้อสอบส่วนใหญ่มีความยากง่ายในระดับปานกลาง (ค่าความยากง่ายเท่ากับ .21-.64) ผลการวิจัยพบว่าในขณะที่ผู้สอบร้อยละ 83.08 รอบรู้คุณลักษณะการอ่านโจทย์ปัญหาที่ซับซ้อนผู้สอบร้อยละ 24.19 รอบรู้คุณลักษณะการให้เหตุผลเชิงวิเคราะห์ผู้สอบต้องรอบรู้คุณลักษณะทั้งหมดจึงจะสามารถตอบข้อสอบส่วนใหญ่ได้ถูกต้อง และผู้สอบที่รอบรู้คุณลักษณะครบทั้ง 8 คุณลักษณะมีเพียงร้อยละ 3.37 ส่วนแนวทางการนำสารสนเทศไปใช้ในการจัดการเรียนรู้นั้น ผู้สอนควรนำกรอบคุณลักษณะทั้ง 8 เป็นแนวในการจัดการเรียนรู้ และจัดการเรียนรู้ให้ตอบสนอง ความต้องการการเรียนรู้ของผู้เรียนตามโปรไฟล์ความรอบรู้ คำสำคัญ: โมเดลวินิจฉัยทางพุทธิปัญญาโมเดลดีไอเอ็นเอการแก้ปัญหา โจทย์ปัญหาทางคณิตศาสตร์ ABSTRACT Word problem solving is very important for the students to link mathematical concepts to real world situation. However, assessment of this construct and use of assessment information are still not promising. This paper aims to analyze student word problem solving by using cognitive diagnostic modeling (CDM) under the integrative framework of cognitive theory and measurement model, and propose guidelines for using diagnostic information for instructional design. The participants were 89 students at grades 5 to 7 from boys and girls clubs in a city of a northwestern state in the USA. Data were collected employing 11 items included in the post-test, mostly selected from the National Assessment of Educational Progress (NAEP) grade 4, with 6 multiple-choice items and 5 constructed-response items. The majority of the items had a difficulty level of medium, ranging from 0.21 to 0.64. The results found that while 83.08% of the examinees possess the attribute of reading problems with complex text, only 24.19% master the analytical reasoning attribute. Most of items require the examinees to possess all assessed attributes to produce the correct answer. Only 3.37% of the total numbers of the examinees master all attributes. The proposed guidelines for using the assessment information suggested that teachers should apply the attributes for instructional focus and provide individualized remedial supports for learning needs based on students’ mastery profile. Keywords: Cognitive diagnostic model, G-DINA model, Problem solving, Word problem